Ancient insights into plant allelopathy and potential applications: new perspectives for sustainable development - Li, Bing; Jiao, Ziheng; Dong, Yuxiao; Wu, Hongjing; Peng, Xuanjie; Zhang, Zilong (Frontiers in Agronomy, 2025)
This review systematically bridges a critical gap in existing scholarship by re-examining plant interaction principles articulated in ancient Chinese agrarian texts through the lens of contemporary allelopathy research. While prior studies have explored allelochemical mechanisms and molecular interactions, this synthesis uniquely focuses on how classical Chinese theories of “mutual engenderment and restraint” offer actionable insights for sustainable agriculture—a dimension underdeveloped in both historical and modern scientific discourse. By cross-referencing ancient documentation of crop interplanting and weed management strategies with current allelopathic research frameworks, this work identifies synergies between traditional ecological wisdom and cutting-edge phytochemical studies. This dual perspective not only validates the empirical foundations of ancient practices but also uncovers innovative solutions for pest suppression, soil health, and yield optimization in resource-constrained agricultural systems. Unlike conventional reviews that compartmentalize historical and scientific analyses, this study demonstrates the translational potential of cultural heritage by modeling a hybrid research methodology that integrates textual philology, ethnobotany, and molecular ecology. This synthesis repositions ethnobotanical heritage as a dynamic resource for harmonizing productivity with ecological balance.